Mapping xylem failure in disparate organs of whole plants reveals extreme resistance in olive roots. Issue 3 (12th March 2018) - Rodriguez‐Dominguez, Celia M.; Carins Murphy, Madeline R.; Lucani, Christopher; Brodribb, Timothy J.
Summary: The capacity of plant species to resist xylem cavitation is an important determinant of resistance to drought, mortality thresholds, geographic distribution and productivity. Unravelling the role of xylem cavitation vulnerability in plant evolution and adaptation requires a clear understanding of how this key trait varies between the tissues of individuals and between individuals of species. Here, we examine questions of variation within individuals by measuring how cavitation moves between organs of individual plants. Using multiple cameras placed simultaneously on roots, stems and leaves, we were able to record systemic xylem cavitation during drying of individual olive plants. Unlike previous studies, we found a consistent pattern of root > stem > leaf in terms of xylem resistance to cavitation. The substantial variation in vulnerability to cavitation, evident among individuals, within individuals and within tissues of olive seedlings, was coordinated such that plants with more resistant roots also had more resistant leaves. Preservation of root integrity means that roots can continue to supply water for the regeneration of drought‐damaged aerial tissues after post‐drought rain. Furthermore, coordinated variation in vulnerability between leaf, stem and root in olive plants suggests a strong selective pressure to maintain a fixed order of cavitation during drought.